Impact of Health Literacy on Medication Adherence: A Systematic Review and Meta-analysis. (June 2014) - Zhang, Ning Jackie; Terry, Amanda; McHorney, Colleen A.
Objective: To systematically review the literature and estimate the effect size of the relationship between health literacy and medication adherence through meta-analysis.Data Sources: Databases searched included Cumulative Index to Nursing and Allied Health Literature (CINAHL; 1982-2013), International Pharmaceutical Abstracts (IPA; 1970-2013), MEDLINE OVID (1966-2013), PubMed (1966-2013), PsycInfo (1966-2013), and Web of Science (1966-2013).Study Selection and Data Extraction: Inclusion criteria were as follows: English language; published through May 1, 2013; medication adherence as the outcome variable; use of validated measures of health literacy and medication adherence; availability of a direct (not mediating) relationship between health literacy and medication adherence; and identifiable effect size and statistical significance of the relationship. Exclusion criteria were as follows: duplicated results, irrelevant results, conference abstracts, proceeding papers, books, dissertations, reviews, editorial letters, continuing education units, or book reviews. Data included author, publication year, disease area, sample size, sampling method, location, study design, effect size of the relationship between health literacy and medication adherence, and measures of health literacy and medication adherence.Data Synthesis: There is a small statistically significant and positive association between health literacy and medication adherence. In the conservative results, the unweighted and weighted correlation coefficients were 0.081 and 0.056 with P values <0.001. In the less conservative results, the unweighted and weighted correlation coefficients were 0.088 and 0.072.Conclusions: The relationship between health literacy and medication adherence is statistically significant but weak. It is plausible that health literacy has a mediator relationship with other adherence determinants. Future research should explore such relationships.